2016
DOI: 10.15388/na.2016.6.3
|View full text |Cite
|
Sign up to set email alerts
|

On new chaotic and hyperchaotic systems: A literature survey

Abstract: This paper provides a thorough survey of new chaotic and hyperchaotic systems. An analysis of the dynamic behavior of these complex systems is presented by pointing out their originality and elementary characteristics. Recently, such systems have been increasingly used in various fields such as secure communication, encryption and finance and so on. In practice, each field requires specific performances with peculiar complexity. A particular classification is then proposed in this paper based on the Lyapunov e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Figure 5 a shows the Poincaré map on z = 0 and Figure 5 b shows the Poincaré maps with initial condition v 2 (0) varying in the range of (−0.08, 0.08), showing that the system’s dynamic behaviors were affected by initial conditions. All the above results verified that System (8) is chaotic [ 23 ].…”
Section: Memcapacitor-based Chaotic Oscillator and Its Dynamicsmentioning
confidence: 67%
“…Figure 5 a shows the Poincaré map on z = 0 and Figure 5 b shows the Poincaré maps with initial condition v 2 (0) varying in the range of (−0.08, 0.08), showing that the system’s dynamic behaviors were affected by initial conditions. All the above results verified that System (8) is chaotic [ 23 ].…”
Section: Memcapacitor-based Chaotic Oscillator and Its Dynamicsmentioning
confidence: 67%
“…Referring to the survey paper [24], the first Lyapunov exponent can be one of the comparative criteria between hyperchaotic systems. Table 3 presents a comparative analysis between system (1) and two related ones, recently proposed in literature.…”
Section: Comparative Analysismentioning
confidence: 99%
“…Some interesting works dealing with parameter identification are covered by Boubaker and Iriarte 73 and Lassoued and Boubaker. 74 In addition, the improvements in the chaotization of FJR manipulators when using robust controllers can be verified. 73 Finally, other studies related to real-world applications of chaotic systems can be found in Boubaker and Jafary.…”
Section: Resultsmentioning
confidence: 95%